Efektivitas Senam Zumba Terhadap Penurunan Efek Samping Kenaikan Berat Badan Pada Akseptor Suntik KB 3 Bulan Di PMB Muslikhatun - Ferika Rahmawati; Yuli Irnawati; Naomi Parmila Hesti Savitri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Injectable contraception does not cause problems but still has drawbacks and side effects. A 3-month injectable birth control acceptor, some time after using the contraception, sometimes experiences several problems such as headaches, menstrual disorders and weight gain or loss. Zumba exercises have movements that are able to move the abdominal and gluteal muscles with light abilities, up to 60 minutes in duration. can break down fat stores in the body. This study aims to determine the effectiveness of Zumba gymnastics on reducing the side effects of weight gain in 3-month injectable birth control acceptors. The design used in this study was quasi-experimental. The research design used was one group pre-test-post test design. The sample in this study was 44 respondents. Data analysis in this study used the Wilcoxon test. The results of the Wilcoxon test above show that a significant value <0.05 with a Zcount value of 3.051 > Z table 0.208 means that H1 is accepted and Ho is rejected, that is, there is an effect of giving Zuma gymnastics on weight loss in 3-month injection family planning acceptors at PMB Muslikhatun.